Traffic differentiation support in vehicular delay-tolerant networks - Soares, V. N.G.J. (2011)
Vehicular Delay-Tolerant Networking (VDTN) is a Delay-Tolerant Network (DTN) based architecture concept for transit networks, where vehicles movement and their bundle relaying service is opportunistically exploited to enable non-real time applications, under environments prone to connectivity disruptions, network partitions and potentially long delays. In VDTNs, network resources may be limited, for instance due to physical constraints of the network nodes. In order to be able to prioritize applications traffic according to its requirements in such constrained scenarios, traffic differentiation mechanisms must be introduced at the VDTN architecture. This work considers a priority classes of service (CoS) model and investigates how different buffer management strategies can be combined with drop and scheduling policies, to provide strict priority based services, or to provide custom allocation of network resources. The efficiency and tradeoffs of these proposals is evaluated through extensive simulation.